High-performance gas sensors with temperature measurement - Zhang, Yong (Nature Publishing Group, 2013)
There are a number of gas ionization sensors using carbon nanotubes as cathode or anode. Unfortunately, their applications are greatly limited by their multi-valued sensitivity, one output value corresponding to several measured concentration values. Here we describe a triple-electrode structure featuring two electric fields with opposite directions, which enable us to overcome the multi-valued sensitivity problem at 1 atm in a wide range of gas concentrations. We used a carbon nanotube array as the first electrode, and the two electric fields between the upper and the lower interelectrode gaps were designed to extract positive ions generated in the upper gap, hence significantly reduced positive ion bombardment on the nanotube electrode, which allowed us to maintain a high electric field near the nanotube tips, leading to a single-valued sensitivity and a long nanotube life. We have demonstrated detection of various gases and simultaneously monitoring temperature, and a potential for applications.